2017
DOI: 10.1111/bjd.15152
|View full text |Cite
|
Sign up to set email alerts
|

The EGALITY study: a confirmatory, randomized, double-blind study comparing the efficacy, safety and immunogenicity of GP2015, a proposed etanercept biosimilar, vs. the originator product in patients with moderate-to-severe chronic plaque-type psoriasis

Abstract: SummaryBackground GP2015 is a proposed etanercept biosimilar. Objectives To demonstrate equivalent efficacy, and comparable safety and immunogenicity of GP2015 and the etanercept originator (ETN, Enbrel â ) in patients with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
159
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(167 citation statements)
references
References 28 publications
5
159
1
2
Order By: Relevance
“…SB4 was approved in regions including Australia, Canada, and the EU based on a submission containing data from a comparative trial in patients with RA, 106,121 while GP2015 has been approved in various markets, including the US, following an application encompassing the results of a trial in psoriasis. 101,122–125 In both cases, approval was granted for other eligible indications of the originator. 125,126 In early 2018, a third etanercept biosimilar, LBEC0101, gained approval in both Japan and the Republic of Korea.…”
Section: Biosimilars Relevant To Inflammatory Conditions: Global Scenmentioning
confidence: 99%
See 1 more Smart Citation
“…SB4 was approved in regions including Australia, Canada, and the EU based on a submission containing data from a comparative trial in patients with RA, 106,121 while GP2015 has been approved in various markets, including the US, following an application encompassing the results of a trial in psoriasis. 101,122–125 In both cases, approval was granted for other eligible indications of the originator. 125,126 In early 2018, a third etanercept biosimilar, LBEC0101, gained approval in both Japan and the Republic of Korea.…”
Section: Biosimilars Relevant To Inflammatory Conditions: Global Scenmentioning
confidence: 99%
“…Data on switching from the originator product to its biosimilar have been provided in the extension phases of comparative clinical studies and in the randomized NOR-SWITCH study, and have not identified any significant safety or efficacy concerns. 122,140142 …”
Section: Biosimilars Relevant To Inflammatory Conditions: Global Scenmentioning
confidence: 99%
“…Therefore, a confirmatory study was conducted to demonstrate equivalent efficacy and similar safety and immunogenicity between GP2015 and reference etanercept in patients with moderate-to-severe chronic plaque-type psoriasis (ClinicalTrials.gov Identifier: NCT01891864) 57 . Patients (n ¼ 531) were randomized 1:1 to receive either GP2015 50 mg or reference etanercept 50 mg twice weekly for 12 weeks.…”
Section: Totality-of-the-evidence Concept For Biosimilaritymentioning
confidence: 99%
“…At Week 12, patients who achieved at least a PASI 50 response were re-randomized to either continue the same treatment on a once-weekly dosing schedule, or to undergo a sequence of treatment switches between GP2015 and reference etanercept until Week 30 ( Figure 5). In the extension phase of the study, patients continued to receive the last treatment that they had received at Week 30 for the remainder of the study until Week 52 57 . The primary efficacy endpoint was the PASI 75 response rate at Week 12, since this measure is well understood and considered clinically meaningful 55 .…”
Section: Totality-of-the-evidence Concept For Biosimilaritymentioning
confidence: 99%
See 1 more Smart Citation